Federal Rules of Civil Procedure - Legal Information Institute; Open Textbook Library (Open Textbook Library, 2016)
These are the Federal Rules of Civil Procedure (FRCP) as amended to December 01, 2016. The FRCP govern civil proceedings in the United States district courts and are often the foundation for the standard 1L law school course, Civil Procedure.
Title I. Scope of Rules; Form of Action -- Title II. Commencing an Action; Service of Process, Pleadings, Motions, and Orders -- Title III. Pleadings and Motions -- Title IV. Parties -- Title V. Disclosures and Discovery -- Title VI. Trials -- Title VII. Judgment -- Title VIII. Provisional and Final Remedies -- Title IX. Special Proceedings -- Title X. District Courts and Clerks: Conduction Business; Issuing Orders -- Title XII. General Provisions -- Appendix of Forms
In English.
Description based on print resource
Keywords: Law -- Textbooks -- United States; Civil Law -- Textbooks; Procedural Law -- Textbooks